MULTI-POINT IMMOBILIZATION OF PENICILLIN G ACYLASE ON SILICA-GLYOXYL: INFLUENCE OF THE DEGREE OF ACTIVATION - PEREIRA,G.H.A. (1997)
Multi-point immobilization, by an intense enzyme-support attachment, may increase the operational stability of a biocatalyst. Penicillin G acylase has many applications, from the hydrolysis of penicillin G (production of 6-aminopenicillanic acid) to the synthesis of semi-synthetic antibiotics. The application of this technique in macroporous silica involves support activation with 3-glycidyloxypropyltrimetoxysilane, followed by acidic hydrolysis and oxidation with sodium periodate. The aldehyde-glyoxyl groups so formed react subsequently with the enzyme. The degree of activation affects the yield and stability of the enzyme immobilization. For 20 UI of enzyme, the results show an immobilization yield equal to 100%, whenever there are more than 140 m Eq of aldehyde groups/g of dry silica. The immobilized enzyme half-life is 23 minutes at 60ºC; under the same conditions, the soluble enzyme has no residual activity after a few minutes. The increase in the degree of activation does not lead to higher stability, which indicates the negative influence of sub-products, formed during the activation of the support